Biology and Management of the Mexican Rice Borer (Lepidoptera: Crambidae) in Rice in the United States. (13th April 2016) - Beuzelin, J. M.; Wilson, B. E.; VanWeelden, M. T.; Mészáros, A.; Way, M. O.; Stout, M. J.; Reagan, T. E.
Abstract: The Mexican rice borer, Eoreuma loftini (Dyar), is an invasive pest of rice, Oryza sativa L., in the Gulf Coast region of the United States. This pest also damages sugarcane, Saccharum spp. hybrids; corn, Zea mays L.; and sorghum, Sorghum bicolor (L.) Moench, and feeds on weedy noncrop grasses. Multiple aspects of integrated pest management including use of pheromone traps, manipulation of planting dates, harvest cutting height, stubble management, noncrop host management, soil fertility management, host plant resistance, use of insecticides, and biological control have been studied for Mexican rice borer management. However, the current management strategy in rice primarily relies on the use of chlorantraniliprole insecticide seed treatments. This profile addresses Mexican rice borer biology and management in rice in the United States.